Economic-emission load dispatch for power system operation using enhanced sunflower optimization - Hazwani Mohd Rosli; Syahirah Abd Halim; Lilik Jamilatul Awalin; Seri Mastura Mustaza (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Conventional thermal power plant uses limited sources of gas, fuel or coal which contributes to the rise of air pollution. Thus, it is crucial to efficiently use the natural sources and minimize the emissions of greenhouse gases and other pollutants. This paper presents an optimal economic dispatch considering three factors which are cost of generation, loss of power transmission and amount of emission for an efficient operation of power generation. Enhanced sunflower optimization (ESFO) algorithm is applied to determine the solution for three different cases: economic load dispatch, emission load dispatch and economic-emission load dispatch. The optimal solution based on the minimum generation cost and emission is obtained for the IEEE 6-unit test system using MATLAB software